Differential expression analysis of miRNAs in macrophage-derived exosomes in the tuberculosis-infected bone microenvironment - Sun, Zhicheng; Pang, Xiaoyang; Wang, Xiyang; Zeng, Hao (Frontiers in Microbiology, 2023)
Background: Macrophages play an important role in regulating the course of spinal tuberculosis within the bone microenvironment. This study aimed to investigate the differential expression of miRNA in macrophage-derived exosomes within the tuberculosis-infected bone microenvironment, to identify miRNAs that hold potential as diagnostic markers and therapeutic targets. Methods: We established study cohorts for spinal tuberculosis, collected bone marrow blood samples, isolated macrophage exosomes, and performed exosome miRNA sequencing. A miRNA-mRNA co-expression network was constructed using WGCNA analysis. Gene GO analysis and KEGG pathway enrichment analysis were performed using KOBAS software. Target miRNAs were selected based on fold change, P value, and false discovery rate, and their validation was carried out using qRT-PCR and ROC curve studies. Subsequently, we constructed a target gene network for these miRNAs and performed KEGG pathway enrichment analysis to explore the potential signaling mechanisms involved in regulating the disease course of spinal tuberculosis. Results: Our findings revealed that macrophages from the tuberculosis-infected bone microenvironment exhibited an M1 phenotype. The successful extraction of exosomes from macrophage supernatants was confirmed through electron microscopy, particle size analysis, and protein blot analysis. Exosome miRNA-seq demonstrated that 28 miRNAs were up-regulated, while 34 miRNAs were down-regulated in individuals with spinal tuberculosis. GO analysis and KEGG pathway enrichment analysis indicated that the differentially expressed miRNAs were involved in various biological processes, cell components, molecular functions, and signaling pathways, which collectively contribute to the regulation of the disease course of spinal tuberculosis. Notably, miRNA-125b-5p was successfully selected based on fold change, p-value, and false discovery rate. qRT-PCR validation further confirmed the significant up-regulation of miRNA-125b-5p in spinal tuberculosis. The ROC curve revealed that miR-125b-5p is a potential diagnostic biomarker for spinal tuberculosis. Moreover, construction of the miRNA-125b-5p target gene network and subsequent KEGG enrichment analysis highlighted the importance of MAPK, TNF, Ras, Rap1, and the PI3K-Akt signaling pathways in the regulation of the disease course of spinal tuberculosis. Conclusion: Our study demonstrates differential expression of miRNAs in macrophage-derived exosomes in the tuberculosis-infected bone microenvironment. Specifically, MiRNA-125b-5p is significantly up-regulated in spinal tuberculosis and shows potential as a diagnostic biomarker for spinal tuberculosis.